2008
DOI: 10.1089/dis.2007.0011
|View full text |Cite
|
Sign up to set email alerts
|

Disease Management Programs for the Underserved

Abstract: Disease management has become an important tool for improving population patient outcomes. The Louisiana State University Health Care Services Division (HCSD) has used this tool to provide care to a largely uninsured population for approximately 10 years. Eight programs currently exist within the HCSD focusing on diabetes, asthma, congestive heart failure, HIV, cancer screening, smoking cessation, chronic kidney disease, and diet, exercise, and weight control. These programs operate at hospital and clinic site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…81,83 Seven studies reported statistically significant increase in the provision of patient education/asthma action plans of 14% to 84% (all reported as statistically significant). 19,36,38,81,[83][84][85] Three of the 4 RCTs reported no significant difference. 45,47,82 SOE: moderate.…”
Section: Decision Supportmentioning
confidence: 96%
See 3 more Smart Citations
“…81,83 Seven studies reported statistically significant increase in the provision of patient education/asthma action plans of 14% to 84% (all reported as statistically significant). 19,36,38,81,[83][84][85] Three of the 4 RCTs reported no significant difference. 45,47,82 SOE: moderate.…”
Section: Decision Supportmentioning
confidence: 96%
“…37,96 Several studies included children. 5,37,46,85,96 Nine studies reported a reduction in ED visits or hospitalizations 5,[36][37][38]46,84,85,95,96 (5%-60%) among pre-post studies (all statistically significant) and 1% to 7% among the RCTs. 5,37,95 SOE: moderate.…”
Section: Clinical Pharmacy Supportmentioning
confidence: 98%
See 2 more Smart Citations
“…TCI management team worked with the LSU system information technology group to design tobaccospecific items for inclusion in its evolving Clinical Inquiry (CliQ) system. 15 It is expected that the number of staff and the time required to document the use of the 5 A's approach will be substantially reduced as CliQ use expands.…”
Section: Guideline Implementation In Public Hospital Systemmentioning
confidence: 99%